Economic education at the expense of indoctrination? Evidence from Germany - Tim Kaiser; Luis Oberrauch (ZBW - Leibniz Information Centre for Economics, 2021)
We study the impact of a recent curriculum reform introducing mandatory economic education in higher-track secondary schools in Southwest Germany. The curriculum reform provides the opportunity to leverage the exogenous variation in exposure to economic education relative to the previous cohort not affected by the reform. One year after exposure to the mandate, we observe positive treatment effects on test scores measuring cognitive elements of economic competence only for students with high test scores at baseline. Two years after exposure to the mandate, we find positive treatment effects on test scores across the entire distribution, as well as socio-emotional skills relevant to financial decision making while we do not observe effects on self-reported financial behaviors. At the same time, we find no changes in social preferences and normative attitudes that could give rise to concerns of indoctrination effects regarding students' views on profit maximization and the market mechanism.
Keywords: A21; G53; I21; 330; Economic education; financial literacy; impact evaluation; social preferences; indoctrination; financial behaviors